2021
DOI: 10.1002/cssc.202002718
|View full text |Cite
|
Sign up to set email alerts
|

Through‐Space Electrostatic Interactions Surpass Classical Through‐Bond Electronic Effects in Enhancing CO2 Reduction Performance of Iron Porphyrins

Abstract: In his pioneering work to unravel the catalytic power of enzymes, Warshel has pertinently validated that electrostatic interactions play a major role in the activation of substrates. Implementing such chemical artifice in molecular catalysts may help improve their catalytic properties. In this study, a series of tetra‐, di‐, and mono‐substituted iron porphyrins with cationic imidazolium groups were designed. Their presence in the second coordination sphere helped stabilize the [Fe−CO2] intermediate through ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 61 publications
0
34
2
Order By: Relevance
“…Curve-crossing is often indicative of an initial induction period where a more active catalytic species is generated in situ and thus its concentration increases as a function of time. 53 Interestingly, curve-crossing was not observed for Fe-para-urea or amide-functionalized analogs, 32 but has appeared in structurally-related urea porphyrins reported by Aukauloo and coworkers, [48][49][50][51] though they did not discuss this observation. Together, these data suggest that curve crossing depends on both the positioning and number of H-bond donors in the second coordination sphere, and hints that ortho urea groups engage in unique interactions during CO2RR.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Curve-crossing is often indicative of an initial induction period where a more active catalytic species is generated in situ and thus its concentration increases as a function of time. 53 Interestingly, curve-crossing was not observed for Fe-para-urea or amide-functionalized analogs, 32 but has appeared in structurally-related urea porphyrins reported by Aukauloo and coworkers, [48][49][50][51] though they did not discuss this observation. Together, these data suggest that curve crossing depends on both the positioning and number of H-bond donors in the second coordination sphere, and hints that ortho urea groups engage in unique interactions during CO2RR.…”
Section: Resultsmentioning
confidence: 97%
“…As such, we reasoned that functionalization of Fe-TPP with a properly-positioned urea moiety would promote advantageous interactions with bicarbonate through templated hydrogen bonding interactions (Figure 1). Integration of urea moieties into porphyrin scaffolds to enhance CO2 reduction through second-sphere hydrogen bonding interactions has been reported by Aukauloo and coworkers [48][49][50][51] but to the best of our knowledge, the anion recognition and templating properties of ureas has not been exploited in CO2 reduction catalysis. We now show that proper positioning of this two-point hydrogen-bond moiety in the second sphere can promote bicarbonate-mediated CO2RR in a well-defined molecular system.…”
Section: Resultsmentioning
confidence: 99%
“…Overpotential ( η ) refers to the additional potential needed to be applied to the system past the thermodynamic potential of the reaction. The high Faraday efficiency of iron porphyrins towards selective CO 2 ‐to‐CO production and their good stability, [26–34] have left most of the design improvements focused on increasing TOF and lowering overpotential.…”
Section: Figures Of Meritmentioning
confidence: 99%
“…Along this line, A. Warshel has decisively demonstrated that electrostatic effects were responsible for the unmatched catalytic power of enzymes [48–50] . With the mindset to interrogate this facet in model complexes, we later varied the number of these cationic groups in catalysts 21 , 22 , and 23 from four, to two, and to one, respectively, and found that the catalytic overpotential is a function of the number of embarked imidazolium groups (ranging from 230 to 430 to 620 mV from tetra‐ to mono‐substituted porphyrin respectively) [34] . This revealed the cumulative nature of through‐space electrostatic effects, as previously observed for through‐bond inductive effects of the fluorine atoms or the cumulative effect of hydrogen bond relays.…”
Section: Going Beyond Electronic Effectsmentioning
confidence: 99%
“…Lessons from the concept of reaction microenvironment in enzymatic catalysis inspire the installation of functional moieties around the active site in proper spatial orientation and distance to interact with bound substrates and thus to exert boosting effects beyond inductive effects on ECR (Figure 3): [43] i) stabilizing key intermediates through intramolecular H‐bonding between bound CO 2 species and pendent Lewis base sites (phenols and amine [44] ), or through electrostatic attraction interaction between bound CO 2 anion and positively charged residues (ammonium [45] and imidazolium cations [46] ), or through Lewis acidic metals; [47] ii) facilitating the protonation of CO 2 anion adduct by virtue of pendant proton donors or local proton source (phenols, [48] imidazolium, [49] thiourea, [50] and carboxylic acid [51] ) or by facilitating H‐bonding network (amine‐NH, [52] imidazolium‐CH, [49] and PEG [53] ); iii) promoting the cleavage of C−O bond via H‐bonding interaction [44,54] . This strategy represents a powerful tool for molecular catalyst optimization and has been effectively used in molecular catalysis to overcome the aforementioned trade‐off.…”
Section: Discrete Molecular Catalysismentioning
confidence: 99%